Optimalisasi Pengelolaan Administrasi Surat Masuk Dan Keluar Pada Bagian Umpeg Dinas Pendidikan Kota Palangka Raya - Rosma Rosma; Slamet Riyadi (JOURNAL SAINS STUDENT RESEARCH, 2025)
Correspondence administration is an essential component that supports effective communication and coordination within governmental institutions. This study aims to describe the process of managing incoming and outgoing letters in the General Affairs and Staffing Division (Umpeg) of the Palangka Raya City Education Office, as well as to identify supporting factors and obstacles encountered during its implementation. This research employs a descriptive qualitative approach through direct observation and active involvement of the researcher during the internship period. The results indicate that letter management has followed a structured workflow consisting of receiving, recording, disposition processing, numbering of outgoing letters, and document archiving. However, the archiving process is still predominantly conducted manually, which leads to longer retrieval time and dependence on staff accuracy. Furthermore, coordination and discipline among staff members were found to play significant roles in ensuring the smooth execution of administrative tasks. The study concludes that although correspondence administration at the Umpeg Division is functioning properly, its efficiency can be further improved through gradual digitalization of archives and enhanced staff competency development.